2022
DOI: 10.1111/jocd.14493
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable changes in beauty market trends focused on the perspective of safety in the post‐coronavirus disease‐19 period

Abstract: Background In February 2020, WHO announced the outbreak of coronavirus disease‐19 (COVID‐19) in a global epidemic, and the COVID‐19 vaccine has recently been developed and approved in many countries to release disease radio waves. Immediately distributed and used to control and control infections. During the COVID‐19 pandemic, the world closed extensively in beauty and beauty services to control the spread of the virus. Objectives Therefore, this study for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 22 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Due to COVID‐19, research on sustainable changes in the safety‐oriented beauty market trend is coming to an era where the perspective of sustainable safety can be applied to the entire beauty and cosmetology industry, and as customers’ perceptions change, safe ingredients are needed. Here, “good ingredients” means safe ingredients according to changes in customers’ perceptions 22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to COVID‐19, research on sustainable changes in the safety‐oriented beauty market trend is coming to an era where the perspective of sustainable safety can be applied to the entire beauty and cosmetology industry, and as customers’ perceptions change, safe ingredients are needed. Here, “good ingredients” means safe ingredients according to changes in customers’ perceptions 22 …”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that, according to changes in customer perception, procurement of raw materials for products beyond raw materials, manufacturing processes, product test, etc. are part of the clean beauty for minimizing carbon emission, using water, recycling product containers, and reducing waste 22 . Lately, as consumers are increasingly interested in products made with safe ingredients, cosmetics that have been certified as vegan are increasing in the cosmetic market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to changes in customer perception, customers will prefer clean beauty to minimize carbon emission, use water, recycle product containers, and reduce waste in the procurement of raw materials for products, manufacturing processes, and product testing beyond raw materials. 36 , 37 , 38 Environmental problems and infectious diseases are changing the situation of women's use of cosmetics around the world. This will require efforts for new changes in the cosmetics market by clearly understanding the needs of consumers in the beauty and cosmetics industry.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is an era where a sustainable safety perspective can be applied to the entire beauty industry today. In addition, according to changes in customer perception, customers will prefer clean beauty to minimize carbon emission, use water, recycle product containers, and reduce waste in the procurement of raw materials for products, manufacturing processes, and product testing beyond raw materials 36–38 . Environmental problems and infectious diseases are changing the situation of women's use of cosmetics around the world.…”
Section: Discussionmentioning
confidence: 99%